(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Latent heat thermal energy storage is one of the most economical ways in which to store the thermal energy for heating air by energy received from the sun. This project is investigation and analysis of thermal energy storage incorporating with action materials (PCM) and integrated solar dish plate to be utilized in solar air heater. Throughout this project reflector plate with stand and paraffin is utilized. The heat storage capability of paraffin is further. Therefore the range of heat energy is enhanced with the help of this reflector. Due to this further amount of heat energy the distinction of water air temperature and outlet air temperature is additional, therefore high temperature of hot air is obtained and efficiency of collector plate is increased. This improved collector efficiency by reducing heat loss to the atmosphere, and facilitate reach an overall efficiency, that accosts of pumping loss for moving air through the collector.